Work engagement, job satisfaction, and turnover intentions: A comparison between supervisors and line-level employees. - Lu, L.; Lu, A.; Gursoy, D; Neale, N. (Emerald Group Publishing Limited, 2016)
Purpose This study aims to investigate the influence of employee positions (supervisor vs. line-level employee) on work related variables (e.g., work engagement, job satisfaction, and turnover intentions). Design/methodology/approach Data were collected from line-level employees and supervisors of 29 mid- to up-scale hotels. A series of one-way ANCOVA were performed to test the position differences in work engagement, job satisfaction, and turnover intentions. Hierarchical regression analyses were conducted to examine the moderating role of employees’ positions on the relationships between those variables. Findings Supervisors have significantly higher work engagement and lower turnover intentions than line-level employees, whereas job satisfaction does not differ across positions. Employee positions significantly moderate the relationship between absorption and job satisfaction, and the relationship between dedication and turnover intentions. Practical implications This study provides an in-depth analysis for hotel managers to capture work-related factors (i.e. work engagement, job satisfaction, and turnover intentions) across employee positions. Dedication is the primary barometer that significantly leads to job satisfaction and reduced turnover intentions, compared to vigor and absorption. Although job satisfaction may be boosted by improving employee work engagement (i.e., vigor, dedication, absorption), increasing absorption is not an effective solution to increase supervisors’ job satisfaction. Hotel managers need to carefully monitor supervisors’ levels of dedication, given its focal impact on turnover intentions. Originality/value This study is one of the first attempts to examine the differences between line-level employees’ and supervisors’ work engagement (i.e. vigor, dedication, absorption) and its consequences (i.e. job satisfaction, turnover intentions). Findings highlight the unique influence of the individual dimension of work engagement on job satisfaction and turnover intentions. This study reveals the moderating effect of employee positions on the links between engagement dimensions and consequences.